Distinct Stress‐Dependent Signatures of Cellular and Extracellular tRNA‐Derived Small RNAs. Issue 17 (4th April 2022) - Li, Guoping; Manning, Aidan C.; Bagi, Alex; Yang, Xinyu; Gokulnath, Priyanka; Spanos, Michail; Howard, Jonathan; Chan, Patricia P.; Sweeney, Thadryan; Kitchen, Robert; Li, Haobo; Laurent, Brice D.; et al.
Abstract: The cellular response to stress is an important determinant of disease pathogenesis. Uncovering the molecular fingerprints of distinct stress responses may identify novel biomarkers and key signaling pathways for different diseases. Emerging evidence shows that transfer RNA‐derived small RNAs (tDRs) play pivotal roles in stress responses. However, RNA modifications present on tDRs are barriers to accurately quantifying tDRs using traditional small RNA sequencing. Here, AlkB‐facilitated methylation sequencing is used to generate a comprehensive landscape of cellular and extracellular tDR abundances in various cell types during different stress responses. Extracellular tDRs are found to have distinct fragmentation signatures from intracellular tDRs and these tDR signatures are better indicators of different stress responses than miRNAs. These distinct extracellular tDR fragmentation patterns and signatures are also observed in plasma from patients on cardiopulmonary bypass. It is additionally demonstrated that angiogenin and RNASE1 are themselves regulated by stressors and contribute to the stress‐modulated abundance of sub‐populations of cellular and extracellular tDRs. Finally, a sub‐population of extracellular tDRs is identified for which AGO2 appears to be required for their expression. Together, these findings provide a detailed profile of stress‐responsive tDRs and provide insight about tDR biogenesis and stability in response to cellular stressors. Abstract : Using AlkB‐facilitated methylation sequencing, this work uncovers the distinct extracellular transfer RNA‐derived small RNA (tDR) fragmentation patterns from cellular tDRs and provides a detailed profile of stress‐responsive tDRs in a variety of cell culture systems and human patients. This work also provides insights about the biogenesis and stability of cellular and extracellular tDRs in response to cellular stressors.